Evaluasi Pelaksanaan Program Pembangunan Jamban Sehat di Kelurahan Temoyong Kecamatan Bulang Kota Batam Tahun 2021 - Wulandari ,; Nazaki ,; Putra , Ardi (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The construction of healthy latrines in Temoyong Village, Bulang Subdistrict, Batam City in 2021 aims to improve clean and healthy lifestyles in the community in defecating. The construction of healthy latrines has not been evenly distributed, there are still a large number of houses that have not received the line from the development. Then, the lack of use of healthy latrines by the community as program recipients. The construction of these latrines is only in the form of toilets, septic tanks, and pipelines that connect the two. This study aims to evaluate the implementation of the healthy latrine development program in Temoyong Village, Bulang Subdistrict, Batam City in 2021. The evaluation carried out is an evaluation of the process, benefits, and consequences arising from the implementation of the healthy latrine development program. The method in this study uses qualitative research methods and uses data collection techniques in the form of observation, interviews, and documentation. The results of the research show that the implementation of the healthy latrine development program has not been running optimally. This can be seen from the process indicators, namely development that is still uneven, and there are still people who get but do not use it so that the targeted number is still not achievable. From the benefit indicator, because the number of availability is still limited, only some people can benefit from this program. Furthermore, from the effect indicator, this healthy latrine development program has received a positive response from all elements of society and related agencies and there has been no rejection. For people who have used it, they can feel the changes that make it easier for the community to dispose of feces without having to fear that the environment will become polluted.